miRNAs in Adipocyte-Derived Extracellular Vesicles: Multiple Roles in Development of Obesity-Associated Disease - Zhou, Yaliang; Tan, Chunlu (Frontiers in Molecular Biosciences, 2020)
Obesity and overweight are common modern health challenges. Caloric intake greater than that needed for energy production results in excess storage of fat in the abdomen. Visceral fat secretes a wide spectrum of adipokines, and increased adiposity is associated with a higher risk of development of metabolic disorders. In addition, adipose tissue secretes extracellular vesicles (EVs) to communicate with peripheral cells and distant organs, and regulate whole-body metabolism. Furthermore, clinical evidence has shown that adipose tissue-derived EVs are present at low levels in the circulation of healthy individuals. In contrast, individuals with metabolic syndrome have significantly higher levels of circulating adipose-derived EVs. The composition of the contents of EVs is dynamic, and closely mirrors individual daily habits and fasting-fed state metabolic characteristics. In this mini-review, we aimed to elucidate the role of adipocyte-derived EVs in regulation of whole-body metabolism under physiological and pathophysiological conditions. Studies have shown that adipose tissue may be a major source of circulating exosomal miRNAs that regulate metabolic homeostasis and directly promote insulin-resistance in other organs. Furthermore, the composition of adipocyte-derived circulating miRNAs in EVs may change prior to development of metabolic disorder. Adipocyte-derived miRNAs in EVs may also induce obesity-related changes such as M1-polarization and inhibition of M2 polarization of macrophages, which may affect the biological behaviors of surrounding tumor cells.